A preliminary study: Effect of initial pH and Saccharomyces cerevisiae addition on biogas production from acid-pretreated Salvinia molesta and kinetics. (15th September 2020) - Syaichurrozi, Iqbal; Basyir, M. Fakhri; Farraz, Rafi Muhammad; Rusdi, Rusdi
Abstract: The aim of this study was to investigate the effect of initial pH and Saccharomyces cerevisiae (SC) addition on biogas yield from acid-pretreated Salvinia molesta (pSM). The initial pH was varied to be 5–8 for substrates without SC (D5-D8) and those with SC addition (DR5-DR8). Before used, Salvinia molesta (SM) was pretreated through sulfuric acid pretreatment. The SC with dose of 1 g for 10 g pSM was added. The results showed that the SC addition increased total biogas yield from 8.49-17.95 mLg −1 -VS (D5-D8) to 58.98–113.71 mLg −1 -VS (DR5-DR8). The methane content in biogas from DR5-DR8 (72.51–84.98%) was higher than that from D5-D8 (6.60–75.03%). The best variable was DR7 (initial pH of 7, SC addition) resulting the highest total biogas yield (113.71 mLg −1 -VS) and methane content (84.98%). The SC contributed in hydrolysis dan acidogenesis phases in biogas production. Then, the modified Gompertz model could predict biogas yield more precise than Cone and first order kinetic models. Percentage fitting error in modified Gompertz, Cone and first order kinetic models was 0.00–3.78%, 0.11–11.81% and 0.36–18.05%. The presence of SC increased the ym (biogas yield potential, mLg −1 -VS), increased the μ (maximum biogas production rate, mLg −1 -VS-d −1 ) and decreased the λ (lag time, d). Highlights: SC contributed in hydrolysis and acidogenesis, increasing VFAs and TAN production. SC addition enhanced not only biogas yield but also methane content. The best condition was initial pH of 7 with SC addition. Modified Gompertz (error 0.00–3.78%) was better than Cone and first order kinetic. SC addition increased biogas production rate (μ) and decreased lag time (λ).